DEVELOPMENT AND EVALUATION OF A DEFECT TRACKING MODEL FOR CLASSIFYING THE INSERTED DEFECT DATA - Sultan, Torky; Khedr, Ayman E.; Sayed, Mostafa (European Scientific Journal, ESJ, 2013)
Defect tracking systems play an important role in the software development organizations as they can store historical information about defects. There are many research in defect tracking models and systems to enhance their capabilities to be more specifically tracking. Furthermore, there are different studies in classifying bugs in a step by step method to have clear perception and applicable method in detecting such bugs. This paper shows a new proposed defect tracking model for the purpose of classifying the inserted defects reports in a step by step method for more enhancement of the software quality. Besides, an evaluation of experiment made for measuring the proposed factors results for defects classification.